Teaching-learning of Science in Online Mode during COVID-19 Lockdown in Rural Schools: Perspectives of Stakeholders of Bolgarh Block of Odisha - Sahoo, Pratyusha Ranjan (SCHOOL SCIENCE, 2020)
Over these years the world has explored many exciting opportunities with new technologies which have changed the trends and have brought people more closely with each other. Innovation has changed the manner in which individuals communicate and cooperate, it has set an open social platform that permits the occupants of this planet earth to interface with one another with ease bringing the whole world under one umbrella. COVID-19 has changed the approach of each sector and forced to change their preferences and needs. Education is one of the important sectors of the country. Looking at the difficulties and challenges faced in teaching-learning process during this period, Government of India as well as state governments are taking many initiatives. One of those initiatives is Odisha Siksha Sanjog launched by Government of Odisha. Based on qualitative design the present study collected data from parents, students and teachers and explores the perspectives of the stakeholders in rural areas on online teaching and learning, its benefits, challenges and possibilities.